Estudio de pre – factibilidad para la creación de una granja agroturística en villa verde, parroquia Chugchilán, cantón Sigchos, provincia de Cotopaxi - Unaucho Chaluisa, Bertha Verónica (2014)
This research proposes publicize the study of Pre - Feasibility Creating a Farm Agro-tourism in Villa Verde, Chugchilán Parish, Sigchos Canton, Cotopaxi Province. The study was conducted through field work and information gathered from primary and secondary source. The market study was prepared for acceptance percentage of tourists who want to visit the farm for recreation, learning and relaxation, can determine their profiles and needs as tourists or students wish to meet, resulting in the real tourists number, after developing the demand, supply and unmet demand for which is the need to integrate the tourism plant, as well as the type of the company logo, slogan and its budget for promotion. Technical survey, where the facilities location and operation of new tourism product, detailing the company size and its services and activities, which were determined, also developed flowcharts to lend services well, noticed also all requirements needs. Equally simple matrix Larry Canter was used, to do the environmental impact study obtaining a reasonable result. Besides the legal framework was done, where the organizational and operational company structure and the human talent number necessary, as well as the rules and laws that must be followed to the constitution was determined....